2023
DOI: 10.1186/s12884-023-05399-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation and deworming during pregnancy reduces the risk of anemia and stunting in infants less than 2 years of age: a study from Sub-Saharan Africa

Abstract: Background In sub-Saharan Africa, infant anemia, stunting and low birth weight remains major public health problems. It is unclear whether prenatal iron supplementation and/or deworming can reduce the risk of infant stunting, anemia and low birth weight. The aim of this study was to investigate the relationship between iron supplementation and/or deworming and stunting, anemia, and low birth weight in infants under two years of age in sub-Saharan Africa. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The present study found an increasing trend of iron supplementation during pregnancy among women of reproductive age in Pakistan with a 44.1% increase in the country, 61.7% increase in rural areas, and 19.9% increase in urban areas since 2006-07 with women of rural areas 0.65 times less likely to uptake iron supplementation during pregnancy when compared to those living in urban areas. The present study found that despite of the increasing trend over the years, the rate of iron supplementation during pregnancy among women in the country stands at 65.4% which is lower than other South Asian countries including Bangladesh (81.0%), India (78.1%), and Nepal (77.0%) [35][36][37] as well as other LMICs including Tanzania (81.6%) and Sub-Sahara Africa (79.7%) [38][39]. However, the rates of the country are relatively higher than that of Ethiopia (60.0%) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The present study found an increasing trend of iron supplementation during pregnancy among women of reproductive age in Pakistan with a 44.1% increase in the country, 61.7% increase in rural areas, and 19.9% increase in urban areas since 2006-07 with women of rural areas 0.65 times less likely to uptake iron supplementation during pregnancy when compared to those living in urban areas. The present study found that despite of the increasing trend over the years, the rate of iron supplementation during pregnancy among women in the country stands at 65.4% which is lower than other South Asian countries including Bangladesh (81.0%), India (78.1%), and Nepal (77.0%) [35][36][37] as well as other LMICs including Tanzania (81.6%) and Sub-Sahara Africa (79.7%) [38][39]. However, the rates of the country are relatively higher than that of Ethiopia (60.0%) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO suggests that in regions with a high prevalence of parasitic infections, combining Fe supplementation with deworming can be an effective approach ( 42 ) . Research conducted in sub-Saharan Africa revealed that administering Fe supplements and deworming treatments during pregnancy resulted in a decreased likelihood of anaemia and stunted growth among infants under the age of two ( 43 ) . In the current analysis, deworming was associated with lower odds of wasting or underweight in the older age group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an analysis of data from the Demographic and Health Surveys revealed that Ethiopian children who were not treated for intestinal parasites were more likely to experience anaemia ( 10 ) . Moreover, administering a deworming treatment with iron supplementation during pregnancy has been shown to reduce anaemia in infants ( 41 ) .…”
Section: Discussionmentioning
confidence: 99%